Efficient production of biallelic GGTA1 knockout pigs by cytoplasmic microinjection of CRISPR/Cas9 into zygotes. (9th September 2016) - Petersen, Bjoern; Frenzel, Antje; Lucas‐Hahn, Andrea; Herrmann, Doris; Hassel, Petra; Klein, Sabine; Ziegler, Maren; Hadeler, Klaus‐Gerd; Niemann, Heiner
Abstract: Background: Xenotransplantation is considered to be a promising solution to the growing demand for suitable donor organs for transplantation. Despite tremendous progress in the generation of pigs with multiple genetic modifications thought to be necessary to overcoming the severe rejection responses after pig‐to‐non‐human primate xenotransplantation, the production of knockout pigs by somatic cell nuclear transfer (SCNT) is still an inefficient process. Producing genetically modified pigs by intracytoplasmic microinjection of porcine zygotes is an alluring alternative. The porcine GGTA1 gene encodes for the α1, 3‐galactosyltransferase that synthesizes the Gal epitopes on porcine cells which constitute the major antigen in a xenotransplantation setting. GGTA1 ‐KO pigs have successfully been produced by transfecting somatic cells with zinc‐finger nucleases (ZFNs), transcription activator‐like effector nucleases (TALENs), or CRISPR/Cas targeting GGTA1, followed by SCNT. Methods: Here, we microinjected a CRISPR/Cas9 vector coding for a single‐guide RNA (sgRNA) targeting exon 8 of the GGTA1 gene into the cytoplasm of 97 in vivo‐derived porcine zygotes and transferred 86 of the microinjected embryos into three hormonally synchronized recipients. Fetuses and piglets were analyzed by flow cytometry for remaining Gal epitopes. DNA was sequenced to detect mutations at the GGTA1 locus. Results: Two of the recipients remained pregnant as determined by ultrasound scanning on day 25 of gestation. One pregnancy was terminated on day 26, and six healthy fetuses were recovered. The second pregnancy was allowed to go to term and resulted in the birth of six healthy piglets. Flow cytometry analysis revealed the absence of Gal epitopes in four of six fetuses (66%), indicating a biallelic KO of GGTA1 . Additionally, three of the six live‐born piglets (50%) did not express Gal epitopes on their cell surface. Two fetuses and two piglets showed a mosaicism with a mixed population of Gal‐free and Gal‐expressing cells. Only a single piglet did not have any genomic modifications. Genomic sequencing revealed indel formation at the GGTA1 locus ranging from +17 bp to −20 bp. Conclusions: These results demonstrate the efficacy of CRISPR/Cas to generate genetic modifications in pigs by simplified technology, such as intracytoplasmic microinjection into zygotes, which would significantly facilitate the production of genetically modified pigs suitable for xenotransplantation. Importantly, this simplified injection protocol avoids the penetration of the vulnerable pronuclear membrane, and is thus compatible with higher survival rates of microinjected embryos, which in turn facilitates production of genetically modified piglets.